PEÑARROCHA FARGAS, MARIELA. Alternativas. Mujeres, género e historia. Barcelona: Universitat de Barcelona, 2020. 246 páginas. ISBN: 978-84-9168-411-4 - Rodríguez, María Salomé (Estudios del ISHiR, 2021)
Alternativas: mujeres, género e historia is a compilation of several research papers by a group of female historians from the University of Barcelona and the University of Valencia. With a pedagogical purpose (to serve as theoretical basis for university degree subjects), they aim to explain the relation between the concepts of gender and history. By means of a variety of texts where different activities are described, roles assumed by men and women are revealed. The book covers a wide periodization: from ancient history to our days, and invites us to reflect on and revise historical, cultural, political and social issues from a gender-aware perspective. This approach is focused on rooting out from the study of human and power relations the idea of what is “natural”.